Discrimination and Recognition of Phantom Finger Sensation Through Transcutaneous Electrical Nerve Stimulation - Li, Mengnan; Zhang, Dingguo; Chen, Yao; Chai, Xinyu; He, Longwen; Chen, Ying; Guo, Jinyao; Sui, Xiaohong (Frontiers in Neuroscience, 2018)
Tactile sensory feedback would make a significant contribution to the state-of-the-art prosthetic hands for achieving dexterous manipulation over objects. Phantom finger sensation, also called referred sensation of lost fingers, can be noninvasively evoked by transcutaneous electrical nerve stimulation (TENS) of the phantom finger territories (PFTs) near the stump for upper-limb amputees. As such, intuitive sensations pertaining to lost fingers could be non-invasively generated. However, the encoding of stimulation parameters into tactile sensations that can be intuitively interpreted by the users remains a significant challenge. Further, how discriminative such artificial tactile sensation with TENS of the PFTs is still unknown. In this study, we systematically characterized the tactile discrimination across different phantom fingers on the stump skin by TENS among six subjects. Charge-balanced and biphasic stimulating current pulses were adopted. The pulse amplitude (PA), the pulse frequency (PF) and the pulse width (PW) were modulated to evaluate the detection threshold, perceived touch intensity, and the just-noticeable difference (JND) of the phantom finger sensation. Particularly, the recognition of phantom fingers under simultaneous stimulation was assessed. The psychophysical experiments revealed that subjects could discern fine variations of stimuli with comfortable sensation of phantom fingers including D1 (phantom thumb), D2 (phantom index finger), D3 (Phantom middle finger), and D5 (Phantom pinky finger). With respect to PA, PF and PW modulations, the detection thresholds across the four phantom fingers were achieved by the method of constant stimuli based on a two-alternative forced-choice (2AFC) paradigm. For each modulation, the perceived intensity, which was indexed by skin indentations on the contralateral intact finger pulp, reinforced gradually with enhancing stimuli within lower-intensity range. Particularly, the curve of the indentation depth vs. PF almost reached a plateau with PF more than 200 Hz. Moreover, the performance of phantom finger recognition deteriorated with the increasing number of phantom fingers under simultaneous TENS. For one, two and four stimulating channels, the corresponding recognition rate of an individual PFT were respective 85.83%, 67.67% and 46.44%. The results of the present work would provide direct guidelines regarding the optimization of stimulating strategies to deliver artificial tactile sensation by TENS for clinical applications.